A qualitative study on pharmacists' perception on integrating pharmacists into private general practitioner's clinics in Malaysia - Saw PS; Nissen L; Freeman C; Wong PS; Mak V (Centro de Investigaciones y Publicaciones Farmaceuticas, 2017)
Background: Private general practitioners in Malaysia largely operates as solo practices - prescribing and supplying medications to patients directly from their clinics, thus posing risk of medication-related problems to consumers. A pharmacy practice reform that integrates pharmacists into primary healthcare clinics can be a potential initiative to promote quality use of medication. This model of care is a novel approach in Malaysia and research in the local context is required, especially from the perspectives of pharmacists. Objective: To explore pharmacists' views in integrating pharmacists into private GP clinics in Malaysia. Methods: A combination of purposive and snowballing sampling was used to recruit community and hospital pharmacists from urban areas in Malaysia to participate either in focus groups or semi-structured interviews. A total of 2 focus groups and 4 semi-structured interviews were conducted. Sessions were audio recorded, transcribed verbatim and thematically analysed using NVivo 10. Results: Four major themes were identified: (1) Limited potential to expand pharmacists' roles, (2) Concerns about non-pharmacists dispensing medicines in private GP clinics, (3) Lack of trust from consumers and private GPs, (4) Cost implications. Participants felt that there was a limited role for pharmacists in private GP clinics. This was because the medication supply role is currently undertaken in private GP clinics without the need of pharmacists. The perceived lack of trust from consumers and private GPs towards pharmacists arises from the belief that healthcare is the GPs' responsibility. This suggests that there is a need for increased public and GP awareness towards the capabilities of pharmacists' in medication management. Participants were concerned about an increase in cost to private GP visits if pharmacists were to be integrated. Nevertheless, some participants perceived the integration as a means to reduce medical costs through improved quality use of medicines. Conclusion: Findings from the study provided a better understanding to help ascertain pharmacists' views on their readiness and acceptance in a potential new model of practice.